Penerapan Model Induktif dan Deduktif untuk Meningkatkan Hasil Belajar Matematika Siswa SD - Intan Mustika Hulu; Ngatini Ngatini; Faradiba Rukmanti; Enjelika Paulina Simarmata; Taruli Marito Silalahi (Pusat Riset dan Inovasi Nasional, 2025)
This scientific article is intended to find out the final results of student learning with inductive and deductive models in elementary school students. The type of article in data collection is a literature review (library research). The source of this research data is secondary data, namely supporting data and complementary research data. The data collection technique for this research is library research. The data analysis technique with the description method, the analysis process used is 3, namely data reduction, data presentation, verification or conclusion. Through this research design, it was produced that: (1) inductive and deductive model learning in mathematics subjects has an effect on student learning outcomes; (2) differences in students' initial talents affect the final results of student learning. The results through the following 2 findings indicate that student learning outcomes in each of their initial abilities are influenced by behavior in applying authentic problem-based learning techniques to inductive-deductive integration. The application of typical problem-based learning empirically can be suspected of being able to provide improvements in student learning outcomes with mathematics learning models.